2022
DOI: 10.3389/fmed.2021.740000
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Previous Caesarean Section and Adverse Maternal Outcomes Accordingly With Robson Classification: Systematic Review and Meta-Analysis

Abstract: Background: The increasing rates of Caesarean section (CS) beyond the WHO standards (10–15%) pose a significant global health concern.Objective: Systematic review and meta-analysis to identify an association between CS history and maternal adverse outcomes for the subsequent pregnancy and delivery among women classified in Robson classification (RC).Search Strategy: PubMed/Medline, EbscoHost, ProQuest, Embase, Web of Science, BIOSIS, MEDLINE, and Russian Science Citation Index databases were searched from 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Our study indicated that women with ≥ 3 previous vaginal have more chances of successful TOLAC. Similar findings were reported in a study conducted by Trojano et al (Trojano et al, 2019) Bishop Score ≥6 was an independent indicator of successful TOLAC (Jamshed et al, 2022). Different studies have evaluated the effect of neonatal birth weight on TOLSC and found that lower estimated birth weight increases the chances of successful TOLAC (Place et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Our study indicated that women with ≥ 3 previous vaginal have more chances of successful TOLAC. Similar findings were reported in a study conducted by Trojano et al (Trojano et al, 2019) Bishop Score ≥6 was an independent indicator of successful TOLAC (Jamshed et al, 2022). Different studies have evaluated the effect of neonatal birth weight on TOLSC and found that lower estimated birth weight increases the chances of successful TOLAC (Place et al, 2019).…”
Section: Discussionsupporting
confidence: 86%